Visit-to-visit blood pressure variability and the risk of stroke in the Netherlands: A population-based cohort study - Alis Heshmatollah; Yuan Ma; Lana Fani; Peter J. Koudstaal; M. Arfan Ikram; M. Kamran Ikram (PLoS Medicine, 2022)
Background Apart from blood pressure level itself, variation in blood pressure has been implicated in the development of stroke in subgroups at high cardiovascular risk. We determined the association between visit-to-visit blood pressure variability and stroke risk in the general population, taking into account the size and direction of variation and several time intervals prior to stroke diagnosis. Methods and findings From 1990 to 2016, we included 9,958 stroke-free participants of the population-based Rotterdam Study in the Netherlands. This is a prospective cohort study including participants aged 45 years and older. Systolic blood pressure (SBP) variability was calculated as absolute SBP difference divided by mean SBP over 2 sequential visits (median 4.6 years apart). Directional SBP variability was defined as SBP difference over 2 visits divided by mean SBP. Using time-varying Cox proportional hazards models adjusted for age, sex, mean SBP, and cardiovascular risk factors, hazard ratios (HRs) for stroke up to January 2016 were estimated per SD increase and in tertiles of variability. We also conducted analyses with 3-, 6-, and 9-year intervals between variability measurement and stroke assessment. These analyses were repeated for diastolic blood pressure (DBP). The mean age of the study population was 67.4 ± 8.2 years and 5,776 (58.0%) were women. During a median follow-up of 10.1 years, 971 (9.8%) participants had a stroke, including 641 ischemic, 89 hemorrhagic, and 241 unspecified strokes. SBP variability was associated with an increased risk of hemorrhagic stroke (HR per SD 1.27, 95% CI 1.05–1.54, p = 0.02) and unspecified stroke (HR per SD 1.21, 95% CI 1.09–1.34, p < 0.001). The associations were stronger for all stroke subtypes with longer time intervals; the HR for any stroke was 1.29 (95% CI 1.21–1.36, p < 0.001) at 3 years, 1.47 (95% CI 1.35–1.59, p < 0.001) at 6 years, and 1.38 (95%CI 1.24–1.51, p < 0.001) at 9 years. For DBP variability, we found an association with unspecified stroke risk. Both the rise and fall of SBP and the fall of DBP were associated with an increased risk for unspecified stroke. Limitations of the study include that, due to an average interval of 4 years between visits, our findings may not be generalizable to blood pressure variability over shorter periods. Conclusions In this population-based study, we found that visit-to-visit blood pressure variation was associated with an increased risk of unspecified and hemorrhagic stroke, independent of direction of variation or mean blood pressure. In a population-based cohort study, Alis Heshmatollah and colleagues investigate the associations between blood pressure variability and risk of stroke among adults in the Netherlands. Author summary Why was this study done? Increased blood pressure is a known and major risk factor of stroke. Growing evidence suggests that, despite hypertension control and medication adherence, visit-to-visit variation in blood pressure is also a risk factor for stroke in high-risk populations. It is not known whether variation in blood pressure is also associated with an increased risk of stroke in the general population. What did the researchers do and find? In this analysis of a prospective cohort study, we followed 9,958 stroke-free participants between 1990 and 2016 and measured blood pressure variation over 2 sequential visits that were an average of 4 years apart. We found that variation of systolic blood pressure, independent of its direction, was associated with an increased risk of stroke, in particular for hemorrhagic and unspecified stroke. Regarding diastolic blood pressure, we found that variation, and in particular a fall but not a rise, in diastolic blood pressure was associated with unspecified stroke. What do these findings mean? Blood pressure variability may be a modifiable risk factor for stroke, and future studies should focus on whether lowering blood pressure variability results in lower stroke incidence.